Penguatan Pendidikan Karakter Melalui Inovasi Media Pembelajaran Berbasis Digital di MAN I Lamongan - Mumtahanah, Nurotun; Suyuthi, Ahmad (Akademika, 2020)
In its development, education and educational institutions must innovate to meet the needs of changing times, the efforts of educational institutions to create and innovate become a necessity and education must be able to keep up with the times. The innovations made by educational institutions are to achieve educational goals for example the competencies that must be mastered by students. In achieving these competencies, it is required capabilities of transmitting so that these competencies could be mastered well by students. One of the educational institution innovating in education and learning is MAN I Lamongan. This research is aimed at finding out digital-based learning media innovation in the development of character education in MAN I Lamongan. Data obtained that digital-based learning media innovation in the development of character education in MAN 1 Lamongan is reflected in three parts. First, The vision and mission of MAN 1 Lamongan; second, learning process by using slides, projected dynamic visuals, prints, games, realia, positive Internet; and third, the Islamic boarding school programs (Ma'had) for male and female students that include the Adiwiyata School Program, the ISO Program, the Prodistic Program equivalent to D1 in collaboration with the Ma'had.